Shaping Better Rehabilitation to Chronic Obstructive Pulmonary Disease Patients: Experiences of Nurses and Colleagues With an Interdisciplinary Telerehabilitation Intervention - Charlotte Simonÿ; Marianne Neerup Andersen; Rasmus Gormsen Hansen; Lisbeth Schrøder; Therese Gjerde Jensen; Uffe Bodtger; Regner Birkelund; Malene Beck (SAGE Publishing, 2022)
In order to evaluate the reach of a collaborative cross-sectoral telerehabilitation intervention to patients with Chronic Obstructive Pulmonary Disease (COPD), this study investigates how nurses and interdisciplinary colleagues experienced working with it. In two focus group interviews, the experiences of working in the empowerment and tele-based > C☺PD-Life >> program were examined among three nurses and four interdisciplinary colleagues. Data were analyzed with inspiration from Ricoeur's theory of narrative and interpretation and discussed with Gittell's theory of relational coordination. Nurses and colleagues experienced that the intervention paved the way for unique patient-professional coordination and interdisciplinary cross-sectoral teamwork that allowed double-layered relational coordination, focusing holistically on patients' lived challenges in everyday life with COPD. By this rehabilitation setup, nurses and colleagues are perceived as educated to deliver high standard personalized support, raising professional pride and confidence. The findings can inspire future health-promoting initiatives within nursing support related to patients afflicted with COPD.